Development of VideoScribe-Based Learning Media on Energy Resources for Grade Four - Sulihan Sulihan; Muhammad Tahir; Hasnawati Hasnawati (Mandalika Institute, 2026)
Technology-based learning media are increasingly needed due to the limited variety of instructional media used by teachers, which often leads to student boredom and reduced enthusiasm during the learning process. This study aimed to develop VideoScribe-based learning media for teaching Energy Resources in Science subjects to fourth-grade elementary school students and to determine its validity and practicality. The novelty of this study lies in the development of VideoScribe-based learning media that integrates animation, narration, text, and contextual illustrations to visualize abstract concepts of energy resources, making science learning more engaging and meaningful for elementary students. The participants were a teacher and fourth-grade students of SDN Sadah, with a small-group trial involving 10 students. This study employed a Research and Development (R&D) approach using the ADDIE model. Data were collected through questionnaires and analyzed using validity and practicality analyses. The material validation score was 93.75% and the media validation score was 100%, both categorized as highly valid. Teacher and student practicality scores reached 95% and 97.29%, respectively, indicating that the media were highly practical. These findings demonstrate that the developed media provides an effective alternative for supporting elementary science instruction by enhancing students' engagement while assisting teachers in explaining abstract scientific concepts.